Algumas reflexões sobre as acessibilidades no Alto Douro - Pina, Maria Helena Mesquita (2014)
The markedly aggressive geographic and morphological structure of the Demarcated Region of the Douro is one of the factors that has hampered the development of the endogenous economy that has found itself, from time immemorial, restricted by extremely deficient accesses both within the region and to the outside. It was only following the "discovery" of the region and, most especially, the internationalisation of Port Wine - a direct dependency between viticultural expansion and its impact on the local economy - that the first steps were taken to improve the roadways, albeit hesitantly so and main-ly in the region known as the Lower Corgo. Improvements in the access to the Demarcated Region were further held back by the epidemics and periods of civil unrest that affected the Port Wine trade. The region had to wait for Fontes Pereira de Melo (the Fontismo period) and his government's policy for expanding the railway network, to be-nefit from better ways to approach it, although the construction of new roads and the upkeep of old roads remained a matter of secondary importance. Unfortunately, neither the undeniable technical advances in the net-work of roads, largely due to the rapid rise in the number of motor vehicles, nor changes in the governments policies were sufficient to reverse the situa-tion. The Douro continued to remain almost inaccessible. In fact, in spite of pressures exerted during the Salazar Regime, it was only in the 60's and espe-cially later, after the 1974 Revolution, that the roads to and within the Demarcated Region were truly improved as the government resorted to funds provided for this purpose by the European Union. This was accompanied by a strategic reorganisation of the entire area that would, from an integrated view-point, ally viticulture to the multiplicity of attractions of this region.